1991
DOI: 10.1247/csf.16.333
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Prostaglandin-Producing Pathway in the Cytotoxic Action of TUmor Necrosis Factor.

Abstract: ABSTRACT. To elucidate the cytotoxic mechanism of tumor necrosis factor (TNF), we isolated TNF-resistant sublines of L929 cells. As compared with L929 cells, TNF-resistant cells retained similar number and affinity of TNF-binding sites, and showed a similar growth rate. TNF stimulated arachidonate release from L929 cells, while no stimulation was observed at all in TNF-resistant cells tested. The cytotoxic action of TNFon L929 cells was inhibited by indomethacin, suggesting that prostaglandin may be involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 30 publications
4
49
1
Order By: Relevance
“…Phospholipase A 2 speci®cally cleaves AA from the sn2 position of membrane phospholipid, which is thereby released from the cells (Clark et al, 1991;Durstin et al, 1994;Hoeck et al, 1993). The TNF-induced lysis of susceptible cells is accompanied by the release of arachidonic acid (AA) into the culture media (Hayakawa et al, 1993). We showed that TNFinduced apoptosis in PBE6 cells was accompanied by increased release of arachidonic acid, indicating that phospholipase A 2 was activated.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Phospholipase A 2 speci®cally cleaves AA from the sn2 position of membrane phospholipid, which is thereby released from the cells (Clark et al, 1991;Durstin et al, 1994;Hoeck et al, 1993). The TNF-induced lysis of susceptible cells is accompanied by the release of arachidonic acid (AA) into the culture media (Hayakawa et al, 1993). We showed that TNFinduced apoptosis in PBE6 cells was accompanied by increased release of arachidonic acid, indicating that phospholipase A 2 was activated.…”
Section: Discussionmentioning
confidence: 93%
“…We showed that TNFinduced apoptosis in PBE6 cells was accompanied by increased release of arachidonic acid, indicating that phospholipase A 2 was activated. Although it has been suggested that cPLA 2 is responsible for this e ect (Hayakawa et al, 1993;Voelkel-Johnson et al, 1996), the involvement of other forms of PLA 2 cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In L929 cells, TNF␣ treatment is known to produce potent cytotoxic effects (14). TNF␣-resistant L929 cells have also been generated via clonal selection from resistant populations of L929 mouse fibroblasts grown in the presence of TNF␣ (14,15). One of these cell lines, C12, differed from the original L929 cells by the absence of cPLA 2 and by the lack of inducibility of AA in response to TNF␣.…”
mentioning
confidence: 99%